The Relationship between Medical Surgical Patients' Perceptions and Nurses' Caring Behavior in the Emergency Room of Hospital X in Jakarta - Susanti, Anisa; Juliani, Enni; Panjaitan, Ribka Sabarina (LPPM Universitas Dhyana Pura, 2025)
Caring behavior is at the core of nursing practice and significantly influences patient satisfaction and perceptions of nursing care. The Emergency Department (ED) is a high-pressure unit that requires nurses to be clinically responsive and consistently demonstrate Caring attitudes. This study aimed to investigate the relationship between medical-surgical patients' perceptions and nurses' Caring behavior in the ED at Hospital X in Jakarta. The study employs a descriptive analytical design with a cross-sectional approach. A total of 91 medical-surgical patients admitted to the ED were selected via porposive sampling. A closed-ended questionnaire was used to measure patients' perceptions of nurses' Caring behavior. Data analysis was performed using the Chi-square test. The results showed that most patients were female (58.2%), between 40 and 49 years old, and had a high school or vocational school education (40.7%). Most patients worked as employees or laborers (38.5%). The Chi-square test results revealed a significant correlation between patients' perceptions and nurses' Caring behavior (p = 0.000). It can be concluded that patients' perceptions of nurses' Caring behavior are influenced by the quality of nurses' interpersonal interactions, empathy, and communication during service delivery. Therefore, improving nurses' Caring behavior in the ED should be a priority to enhance the quality of nursing care.